The maturity model of logistic centres - Krys Piotr P.; Izdebski Waldemar (2022)
Objectives: The main aim of the article is to present the authors' model of the maturity of logistic centres, in its original, previously published version and improved for the purpose of testing the reliability of logistic centre characters. The second purpose of the article is to justify the possibility of using the maturity model to ensure the reliability of logistic centres. Methods: To carry out the research and prepare the article, an expert (Delphic) method was used, using the knowledge of experts professionally connected with logistic centres, and a literature review. Results: The conclusion of the research and analysis of the results is an improved model of logistic centre maturity compared to previous work. Conclusion: The developed model of logistic centre maturity allows for a comprehensive analysis of the logistic centre's maturity, locating points in need of improvement, and allows continuity and reliability of the centre's operation to be ensured. Highlights: - The reliability of logistic centres is extremely important for supply chains - The maturity model of logistic centres allows for a comprehensive analysis of the examined centre - Maturity models are an accepted method of ensuring business reliability - The maturity model developed helps to ensure the reliability of the centres